Human umbilical artery smooth muscle exhibits a 2-APBsensitive capacitative contractile response evoked by vasoactive substances and expresses mRNAs for STIM, Orai and TRPC channels - Roldan Palomo, Ana Rocio (2012)
After depletion of intracellular Ca2+ stores the capacitative response triggers an extracellular Ca2+ influx through store-operated channels (SOCs) which refills these stores. Our objective was to explore if human umbilical artery smooth muscle presented this response and if it was involved in the mechanism of serotonin- and histamine-induced contractions. Intracellular Ca2+ depletion by a Ca2+-free extracellular solution followed by Ca2+ readdition produced a contraction in artery rings which was inhibited by the blocker of Orai and TRPC channels 2-aminoethoxydiphenyl borate (2-APB), suggesting a capacitative response. In presence of 2-APB the magnitude of a second paired contraction by serotonin or histamine was significantly less than a first one, likely because 2-APB inhibited store refilling by capacitative Ca2+ entry. 2-APB inhibition of sarcoplasmic reticulum Ca2+ release was excluded because this blocker did not affect serotonin force development in a Ca2+-free solution. The PCR technique showed the presence of mRNAs for STIM proteins (1 and 2), for Orai proteins (1, 2 and 3) and for TRPC channels (subtypes 1, 3, 4 and 6) in the smooth muscle of the human umbilical artery. Hence, this artery presents a capacitative contractile response triggered by stimulation with physiological vasoconstrictors and expresses mRNAs for proteins and channels previously identified as SOCs.